A RARE CASE OF SCRUB TYPHUS MASQUERADING AS BREAST ABSCESS - Krishna, Venkata Pothukuchi; Chepuri, Venkata Ravikumar; Kanumuri, Sudhakar; Yarram, Raghavareddy; Yadalla, Sailaja (Journal of Health and Allied Sciences NU, 2014)
We are presenting a case of scrub typhus masquerading as breast abscess in a pregnant woman who attended to hospital with history of fever and breast tenderness. A high index of suspicion is necessary as it is rarely seen but easily treatable and without proper and timely treatment, serious complications may arise which carries high mortality rate. Scrub typhus during pregnancy is quite rare. The line of treatment of scrub typhus in pregnancy is also analysed.
Keywords: Scrub typhus; eshcar; breast abscess